Mangroves: a model for an ecosystemic scene (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article investigated how theatre can engage with the current context of socio-ecological crises, offering reflections that may underpin artistic practices aimed at expanding relational modes and proposing new forms of sensibility. To this end, a systemic methodology was proposed as a condition of possibility for the creation of ecosystemic scenes. The theatrical modelling of natural complex systems, such as the mangrove ecosystem, was presented as a strategy for fostering awareness of the ecological crisis. Some considerations on this premise were developed based on the workshops conducted by the author.
Keywords: mangroves; modelling; ecosystemic theatrical scenes